Analisis Technology Acceptance Model terhadap perilaku penguna mobile banking di Surakarta - Agus Setiawan; Ria Aris Belianti; Tri Wulandari (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This study aims to analyze how banking customers receive mobile banking services and their behavior in using them. This study aims to analyze the application of the Technology Acceptance Model (TAM) involving perceived usefulness, behavioral intention to use, and attitude toward using as intervening variables on consumer behavior in mobile banking in Surakarta. This study uses a quantitative method with primary data obtained by distributing online questionnaires to banking customers who use mobile banking services. The analysis technique used is Structural Equation Modeling – Partial Least Square (SEM-PLS). The result showed that H1, H2, H3, H5, H6 and H7 were accepted and H4 was rejected. This research is expected to be useful as additional information is needed to improve service to customers.